Hijab: Kewajiban Religius atau Pilihan Identitas? Studi pada Mahasiswi Muslim Jurusan Bahasa dan Sastra Indonesia Universitas Negeri Medan - Hapni Laila Siregar; Ayla Zahra Adnan; Muhammad Fadhil Romadhon; Najla Mutia Nasution; Sarah Meutia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the practice and meaning of hijab among Muslim female students in the Indonesian Language and Literature Department to determine whether the hijab is understood more as a religious obligation or as a form of identity choice. The purpose of this study is to describe the motivations, patterns of practice, social influences, and experiences of female students related to wearing the hijab in their daily lives, both on and off campus. The study employed a quantitative-descriptive design complemented by qualitative components. A structured questionnaire consisting of Likert-scale statements and open-ended questions was distributed to 70 Muslim female students, while essay responses were analyzed thematically to gain a deeper understanding of the respondents’ perspectives. Quantitative data were summarized using descriptive statistics in the form of percentage distributions to identify response tendencies, while qualitative data were coded to present representative experiences, views, and reasons underlying the decision to wear the hijab. The results showed that the majority of female students consistently wore the hijab primarily because of religious beliefs and personal awareness as Muslim women, although cultural identity, family environment, and social acceptance also influenced the practice. The implications of this study emphasize the importance of recognizing the hijab as both a manifestation of faith and a social identity, as well as the need for a campus environment that respects individual motivations, choices, and autonomy in wearing the hijab.